Negative Correlation between cross-linked fibrin degradation products (d-dimer) and glasgow coma scale (GCS) scores in patients with head injury - Setyawati, Andriani Tri Susilowati Usi Sukorini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Traumatic Brain Injury (TBI) is damage in the brain caused by a traumatically injuring external force. To observe its severity, the Glasgow Coma Scale (GCS) and Computed Tomography (CT) scan are used. In addition, D-dimer as an end product of fibrinolytic activity is proposed as the predictor of TBI outcome. The increase of D-dimer value is correlated with severity. CT-scan is too expensive and requires patientsâ mobility that can cause worse incidents. The aim of this study was to correlate between D-dimer and GCS in patients with traumatic brain injury. The cross sectional observational analytic design was carried out in the study. The TBI patients with 24 hours onset admitted to Emergency Room Dr. Sardjito Hospital Yogyakarta will be included with inclusion and exclusion criteria consecutively. Glasgow coma scale was measured and plasma D-Dimer was examined using Nycocard with immunofiltration method. Correlation between plasma D-Dimer and Glasgow Coma Scale was tested using Pearson Correlation when the population distribution was normal and Spearman when it was not normally distributed. There was a strong negative correlation between D-dimer and Glasgow Coma Scale (r=-0.622; p<0.001) and Prothrombin Time with D-dimer value (r=0527; p<0.001). Moreover, it was found that haemoglobin had a correlation with D-dimer (r=-0.517; p=0.001). Haemoglobin and PT had a correlation with Glasgow Coma Scale (r=0.419 vs -0.591; p<0.001) and neutrophil had poor correlation with Glasgow Coma Scale (r=-0.336; p=0.034). In conclusion, there was a strong negative correlation between degradation product of cross-linked fibrin (D-dimer) and Glasgow Coma Scale in patients with traumatic brain injury. Keywords: D-Dimer - Glasgow Coma Scale - Traumatic Brain Injury - CT scan - correlation